2019
DOI: 10.5860/crl.80.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Evolving and Enduring Patterns Surrounding Student Usage and Perceptions of Academic Library Reference Services

Abstract: This descriptive study analyzes results from an 18-item survey that assessed students' usage and perceptions of library reference services at a comprehensive public metropolitan university. Among 235 surveys completed between November 2016 and January 2017, the majority of respondents represented the "Generation Z" population of college students, 18 to 24 years of age. Quantitative and qualitative findings revealed patterns of reference service usage, perceptions of librarians, and barriers and facilitators to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, perceptions of librarian teaching skills might be expanding. Jameson, Natal, and Napp (2019) found the top reason students asked a librarian for help was 'to learn how to use a library resource' (48%), which outranked 'to get help finding books' (46%), and 'to get help finding articles' (33%) (p. 373). And Meredith and Mussel found that 'figuring out how to narrow your search results' was the top area improved by embedded librarian tips and forum discussion, outranking 'figuring out which are the best search tools to use for your topic' (2014, p. 97).…”
Section: What Librarians Know: Librarian Expertise and Skills / Valuementioning
confidence: 99%
See 4 more Smart Citations
“…However, perceptions of librarian teaching skills might be expanding. Jameson, Natal, and Napp (2019) found the top reason students asked a librarian for help was 'to learn how to use a library resource' (48%), which outranked 'to get help finding books' (46%), and 'to get help finding articles' (33%) (p. 373). And Meredith and Mussel found that 'figuring out how to narrow your search results' was the top area improved by embedded librarian tips and forum discussion, outranking 'figuring out which are the best search tools to use for your topic' (2014, p. 97).…”
Section: What Librarians Know: Librarian Expertise and Skills / Valuementioning
confidence: 99%
“…This literature review found significant interest in the question of how students perceive librarians' affect, and how that influences whether they ask for help (Table 14). Jameson et al (2019) found students at one institution rated librarians as 'very approachable' or 'approachable' 79% of the time, with 16% choosing 'slightly approachable' (p. 375). However, the researchers noted that many of their respondents had also indicated they couldn't tell who a librarian was, so these responses might reflect impressions of library workers generally.…”
Section: What Librarians Are Like: Motivations and Affective Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations